Home-Based Virtual Reality-Augmented Training Improves Lower Limb Muscle Strength, Balance, and Functional Mobility following Chronic Incomplete Spinal Cord Injury - Villiger, Michael; Liviero, Jasmin; Awai, Lea; Stoop, Rahel; Pyk, Pawel; Clijsen, Ron; Curt, Armin; Eng, Kynan; Bolliger, Marc (Frontiers in Neurology, 2017)
Key factors positively influencing rehabilitation and functional recovery after spinal cord injury (SCI) include training variety, intensive movement repetition and motivating training tasks. Systems supporting these aspects may provide profound gains in rehabilitation, independent of the subject’s treatment location. In the present study, we test the hypotheses that virtual reality (VR)-augmented training at home (i.e. unsupervised) is feasible with subjects with an incomplete SCI (iSCI), and that it improves motor functions such as lower limb muscle strength, balance and functional mobility. In the study, 12 chronic iSCI subjects used a home-based, mobile version of a lower limb VR training system. The system included motivating training scenarios and combined action observation and execution. Virtual representations of the legs and feet were controlled via movement sensors. The subjects performed home-based training over four weeks, with 16 to 20 sessions of 30 to 45 minutes each. The outcome measures assessed were the Lower Extremity Motor Score (LEMS), Berg Balance Scale (BBS), Timed Up and Go (TUG), Spinal Cord Independence Measure (SCIM mobility), Walking Index for Spinal Cord Injury (WISCI II), 10 Meter and 6 Minute Walking Tests (10MWT and 6minWT). Two pre-treatment assessment time points were chosen for outcome stability: four weeks before treatment and immediately before treatment. At post-assessment (i.e. immediately after treatment), high motivation and positive changes were reported by the subjects (adapted Patients’ Global Impression of Change). Significant improvements were shown in lower limb muscle strength (LEMS, P = 0.008), balance (BBS, P = 0.008) and functional mobility (TUG, P = 0.007). At follow-up assessment (i.e. 2-3 months after treatment), functional mobility (TUG) remained significantly improved (P = 0.005) in contrast to the other outcome measures. In summary, unsupervised exercises at home with the VR training system led to beneficial functional training effects in subjects with chronic iSCI, suggesting that it may be useful as a neurorehabilitation tool.